Dukungan Sosial dalam Bentuk Pesta Sekolah dengan Motivasi Berprestasi Mahasiswa Manggarai - Fransiskus Natali Agatio Nanu; Dian Lestari Anakaka; Shela Christine Pello (Journal of Health and Behavioral Science, 2019)
Pesta Sekolah are events in social community in Manggarai when the community member wants to continue their studies but are constrained by costs. Pesta Sekolah is a form of social support in the Manggarai community which is reflected in the form of caring and assistance both morally and materially to fellow members. There are Manggarai students who continue their studies at tertiary institutions who have outstanding achievements, however not frequently there are students who do not complete their studies. This study aims to analyze the relationship of social support in the form of a school party with achievement motivation in Manggarai students in Kupang City. The research type is quantitative research. The population is taken based on criteria while sampling uses a total sampling of 71 students from three Manggarai regional organizations in Kupang City. Analysis using Product Moment Pearson Correlation shows that there is a significant relationship between social support in the form of Pesta Sekolah and achievement motivation (r= 0.680; ƿ <0.05).